Stratified Probabilistic Bias Analysis for Body Mass Index–related Exposure Misclassification in Postmenopausal Women. Issue 5 (September 2018) - Banack, Hailey R.; Stokes, Andrew; Fox, Matthew P.; Hovey, Kathleen M.; Cespedes Feliciano, Elizabeth M.; LeBlanc, Erin S.; Bird, Chloe; Caan, Bette J.; Kroenke, Candyce H.; Allison, Matthew A.; Going, Scott B.; Snetselaar, Linda; et al.
Abstract : Background: There is widespread concern about the use of body mass index (BMI) to define obesity status in postmenopausal women because it may not accurately represent an individual's true obesity status. The objective of the present study is to examine and adjust for exposure misclassification bias from using an indirect measure of obesity (BMI) compared with a direct measure of obesity (percent body fat). Methods: We used data from postmenopausal non-Hispanic black and non-Hispanic white women in the Women's Health Initiative (n=126, 459). Within the Women's Health Initiative, a sample of 11, 018 women were invited to participate in a sub-study involving dual-energy x-ray absorptiometry scans. We examined indices of validity comparing BMI-defined obesity (≥30 kg/m 2 ), with obesity defined by percent body fat. We then used probabilistic bias analysis models stratified by age and race to explore the effect of exposure misclassification on the obesity–mortality relationship. Results: Validation analyses highlight that using a BMI cutpoint of 30 kg/m 2 to define obesity in postmenopausal women is associated with poor validity. There were notable differences in sensitivity by age and race. Results from the stratified bias analysis demonstrated that failing to adjust for exposure misclassification bias results in attenuated estimates of the obesity–mortality relationship. For example, in non-Hispanic white women 50–59 years of age, the conventional risk difference was 0.017 (95% confidence interval = 0.01, 0.023) and the bias-adjusted risk difference was 0.035 (95% simulation interval = 0.028, 0.043). Conclusions: These results demonstrate the importance of using quantitative bias analysis techniques to account for nondifferential exposure misclassification of BMI-defined obesity. See video abstract at, http://links.lww.com/EDE/B385 . Abstract : Supplemental Digital Content is available in the text.